Smart Accident Detection and Alerting System - ANAK JOHNY, KRISTO BLUN; BIN ISHAK, MAIZUL (Progress in Engineering Application and Technology, 2023)
Accident can take place any time any day, especially when the road is busy. Sometimes it happens due to the driver’s negligence, the road conditions, or the state of the vehicle. Regardless, when an accident does occur time is at the essence. Responds time for rescue personnel to get to the accident site will be an issue. When an accident happens at a road less travels and the driver is unconscious, it will take much longer time. Even if there is a passer-by, it will take them time also to assess the situation before calling for help. By creating this system, it will reduce time taken for help to arrive. Once an accident occurs, the accelerometer will trigger the Arduino Nano, then it will receive input from the GPS module then Arduino Nano will send signal to GSM module to instantly request for aid.